Improving Students' English Speaking Skills through Group Discussions: A Qualitative Approach - Eka Desy Asgawanti; Ilona Vicenovie Oisina Situmeang; Angga Priyatna (CV. Mitkom Indotama, 2025)
This study aims to explore the influence of group discussions on the improvement of students' speaking skills in English. Using a qualitative approach with a case study method, this research involves 15 students who participated in group discussions in the English class. Data were collected through in-depth interviews and direct observations during the discussion sessions. The research results show that group discussions significantly enhance students' confidence, comfort, and engagement in communication. As many as 80% of respondents reported an increase in confidence, while 75% felt more comfortable expressing their ideas. Additionally, the frequency of verbal interactions increased by 60%, indicating that students are more actively participating in discussions. These findings affirm that the collaborative environment created through group discussions contributes to the development of speaking skills. This research has practical implications for English language teaching, where group discussion methods can be integrated into the curriculum to enhance students' speaking skills. Keywords: Speaking Skill, Interpersonal Communication and Collaborative Learning